Effect of antioxidants on properties of rice flour/cassava starch film blends plasticized with sorbitol - Pornchai Rachtanapun (2018)
The effects of antioxidants (gallic acid (GA), propyl gallate (PG) and butyl hydroxyanisole (BHA)) on the mechanical properties, water solubility and melting point temperature (Tm) of rice flour/cassava starch film blends with sorbitol were investigated. All films forming a solution were casted and dried at room temperature. Film blended with GA (400 mg) showed higher tensile strength and folding endurance, but lower %elongation than the control film blend. The tensile strength of film blended with PG and film blended with BHA were not significantly different (p>0.05) compared with the control film. Film blended with GA showed higher water solubility than the control film, film blended with PG and film blended with BHA, respectively, because GA had a higher polarity than PG and BHA, respectively. Differential scanning calorimeter (DSC) thermographs showed a single peak for all film blends with and without antioxidants, confirming their homogeneity. Changes in the Tm of film blends with antioxidants depended upon the Tm of the antioxidants.